The Role of Campus Servicescape in Fostering New Student Interest at Islamic Private Universities - Bachtiar Hariyadi; Nurardiansah, Ibnu Helga (Journal of Educational Management Research, 2025)
This study aims to examine prospective students' perceptions of the physical appearance and atmosphere of the campus (servicescape) and its impact on their interest in choosing Islamic Private Universities (IPU). Employing a qualitative phenomenological approach, data were collected through observation, in-depth interviews, and document analysis, and were thematically analyzed. The findings revealed four main themes: initial impressions based on cleanliness and Islamic symbols, emotional comfort, representation of Islamic values, and campus aesthetics reflecting institutional professionalism. These four aspects contribute to a positive perception that influences students’ interest. The results, supported by subject triangulation, highlight the importance of a calm, religious, and well-organized campus environment in promotional strategies and the development of Islamic character. The implications of this study suggest that the management of campus servicescapes, which reflects Islamic values and creates a comfortable atmosphere, can enhance prospective students' interest in choosing Islamic Private Universities. Therefore, IPUS must focus on cleanliness, aesthetics, and Islamic symbols in its marketing strategies.